2020
DOI: 10.1161/strokeaha.119.027549
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Variability and Neurologic Outcome After Endovascular Thrombectomy

Abstract: Background and Purpose— Although higher blood pressure variability (BPV) is associated with worse functional outcome after stroke, this association is not as well established in large vessel occlusion strokes treated with endovascular treatment (EVT). Methods— In this post hoc analysis of BEST (Blood Pressure after Endovascular Therapy for Ischemic Stroke), a prospective, multicenter cohort study of anterior circulation acute ischemic stroke patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(144 citation statements)
references
References 37 publications
8
136
0
Order By: Relevance
“…Blood pressure management is a key challenge in acute ischemic stroke treatment, especially in patients who achieve successful reperfusion with endovascular therapy. Cumulative evidence supports a link between higher BP on admission or after MT and worse functional outcome 3–7. However, the effect of SBPr in the first 24 hours on outcome after successful reperfusion is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood pressure management is a key challenge in acute ischemic stroke treatment, especially in patients who achieve successful reperfusion with endovascular therapy. Cumulative evidence supports a link between higher BP on admission or after MT and worse functional outcome 3–7. However, the effect of SBPr in the first 24 hours on outcome after successful reperfusion is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is common among patients with stroke and especially those presenting with acute ischemic stroke owing to large vessel occlusions 1 2. Many studies investigating the relation between blood pressure (BP) and outcome after mechanical thrombectomy (MT) have reported a significant association between higher BP and poor outcome,3–7 a finding that is consistent with studies from before the thrombectomy era 8 9. However, the relationship between systolic BP reduction (SBPr) and outcome of MT has not been studied.…”
Section: Introductionmentioning
confidence: 97%
“…For example, incomplete recanalization may result in increased intracranial vascular resistance and subsequent blood pressure variability ( 47 ). Likewise, patients who present with less blood pressure variability experience better short-term ( 48 ) and long-term ( 49 ) functional outcomes. Blood pressure variability can be measured using several statistical formulas, including standard deviation (SD), coefficient of variation, successive variation (SV), and average real variation (ARV).…”
Section: Hemodynamics and Pathophysiology Of Lvo Strokesmentioning
confidence: 99%
“…Our group has demonstrated poor discharge outcomes among successfully recanalized patients who had sustained hypoperfusion for >12 hours, as well as those with higher blood pressure variability in the first 24 hours following MT ( 69 , 48 ). Similarly, in a post-hoc analysis of the BEST trial data, the patients with higher blood pressure variability within the first 24 hours had poor 90-day functional outcomes ( 49 ).…”
Section: Current Guidelinesmentioning
confidence: 99%
“…Blood pressure variability (BPV) is one of the factors that related to prognosis of ischemic stroke. Several studies suggested that increased BPV was associated with poor neurologic outcome, [14][15][16] while the mechanism behind is not fully understood. Researches on hypertension suggested injured endothelium due to highly fluctuating abnormal blood flow related to vascular inflammation, 17,18 and meanwhile accumulating evidence suggested inflammation played a central role in all aspects of stroke including its initiation and progression.…”
Section: Introductionmentioning
confidence: 99%